Kupffer cells are essential for platelet-mediated thrombopoietin generation in the liver - Danielle Karakas; June Li; Wenjing Ma; Xun Grace Wu; Christopher J. Khoury; Mina Masoud; Brock Hoard; Yuning Jay Liu; Guangheng Zhu; Junmei Chen; Martha Sim; Chuanbin Shen; et al. (Proceedings of the National Academy of Sciences, 2025)
Thrombopoietin (TPO), predominantly produced by the liver, is the key regulator for platelet production and the hematopoietic stem cell niche. Our earlier report demonstrated that platelet GPIbα is required for hepatocellular TPO generation, which is the major resource of TPO in the blood circulation. However, how hepatocytes physically contact circulating sinusoidal platelets across the liver endothelium for this process is unknown. Kupffer cells reside in contact with both sinusoidal blood and underlying hepatocytes, and mediate senescent platelet clearance, but their role in TPO regulation has never been explored. Here, we found Kupffer cell depletion via either clodronate liposomes or specific transgenic models abrogated circulating TPO. Kupffer cell depletion also prevented TPO level increase in GPIbα-deficient mice following wild-type (GPIbα + ) platelet transfusion, signifying an interdependent mechanism for TPO regulation. Mice treated with arsenite had significantly decreased liver endothelial fenestrations and hepatocyte sinusoidal protrusions as well as TPO levels. This effect was exacerbated by Kupffer cell depletion, and Kupffer cells were identified to enhance liver endothelial fenestrations. Electron microscopy and immunofluorescence analysis of the liver revealed platelets arrested on Kupffer cell surface were in contact with hepatocyte protrusions. Thus, we elucidated that Kupffer cells promote endothelial fenestrae and hepatocyte protrusions, accumulate circulating platelets, and facilitate cellular interactions between hepatocytes and platelets, which drive TPO generation. This connection between platelet clearance and thrombopoiesis should have broad implications for hematology and pathologies such as Bernard–Soulier syndrome, thrombocytopenias, as well as liver diseases.